Features of home schooling in the Republic of Belarus - Ksionda, Olga G.; Kovtunenko, Ekaterina O. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The paper considers the concepts of home (family) education, the features of its existence in the Republic of Belarus. The problems and features of this type of training are described. The results of interviews with children who study at home on an individual plan and their parents are considered. The analysis of the attitude of parents and children to school education is presented, the values and goals of home schooling are summarised, the motivation for teaching children working according to an individual plan is characterised.